2017
DOI: 10.11646/phytotaxa.311.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Nupela major sp. nov., a new diatom species from Maolan Nature Reserve, central-south of China

Abstract: Nupela major sp. nov., a new species of the diatom genus Nupela, is described from Maolan Nature Reserve, Guizhou Province, China. Observations were made using light and scanning electron microscopy documenting the size, shape and ultrastructure of the new species. Valves of the monoraphid frustules are elliptical-lanceolate with more or less cuneate, subtlety protracted ends. The raphe valve has a linear-lanceolate axial area and an irregularly-shaped central area. Striae appear intermittent or disrupted. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…In the sample we studied here, two large species may be found, Nupela major (Yu et al . ) and A. maolanensis (both taxa having cells that are more than 30 μm long, with the largest cells reaching up to 90 μm in length). Most of the other species in this sample are very small, less than 20 μm long, for example Achnanthidium spp., Sellaphora spp., and Navicula spp., among others.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the sample we studied here, two large species may be found, Nupela major (Yu et al . ) and A. maolanensis (both taxa having cells that are more than 30 μm long, with the largest cells reaching up to 90 μm in length). Most of the other species in this sample are very small, less than 20 μm long, for example Achnanthidium spp., Sellaphora spp., and Navicula spp., among others.…”
Section: Discussionmentioning
confidence: 99%
“…As a part of our continuing study of the freshwater diatoms of Guizhou Province, China (Kociolek et al 2016a(Kociolek et al , 2016bYou et al 2016You et al , 2017Lowe et al 2017;Yu et al 2017), we encountered a species of Achnanthes for which we can find no previous description. The purpose of the present report is to present light and scanning electron microscope observations of this Achnanthes species from Guizhou, and to offer a formal description of it as a species new to science.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the laboratory, diatom samples were cleaned with concentrated nitric acid using the Microwave Accelerated Reaction System (Model MARS, CEM Corporation, Charlotte, USA) (Parr et al 2004), with a pre-programmed digestion scheme (temperature, 180℃) (You et al 2015;Yu et al 2017). Next, samples were alternately centrifuged for 5 min at 3500 rpm (TDZ5-WS, Luyi Corporation, Shanghai, China) and washed six times using distilled water until the pH of the sample was close to neutral.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, more than 200 Achnanthidium species have been reported in the literature worldwide (Marquardt et al 2017, Yu et al 2019. In China, roughly 60 Achnanthidium species have been reported (Liu et al 2013, Wang & Deng 2017, Yu et al 2017, but only a few have been reported as new species (Yu et al 2018, 2019, Liu et al 2016.…”
Section: Introductionmentioning
confidence: 99%